Beneficial role of Azolla sp. in paddy soils and their use as bioremediators in polluted aqueous environments: implications and future perspectives. Issue 9 (29th July 2021) - Akhtar, Muhammad; Sarwar, Nadeem; Ashraf, Arooba; Ejaz, Amjad; Ali, Shafaqat; Rizwan, Muhammad
ABSTRACT: Azolla is a free-floating hydrophyte fern grown in temperate and tropical regions. The specialized dorsal leaves of the fern possess cavity that harbors cyanobacteria capable of fixing atmospheric nitrogen (N) through biological processes. It is either incorporated into the soil before rice transplantation or grown as an inter-crop with rice crop. Its intercropping also improves efficiency of applied N fertilizer. The recovery of heavy metals from aqueous environment is another key feature of Azolla as bioremediator of flooded soils. In general, Azolla efficiently absorbs heavy metals from aqueous medium containing lower concentrations (<20 mg L -1 ); however, filiculoides species were found to absorb higher metal content (0.40% Ni) from Ni rich solution (500 mg L -1 ). Biosorption involves biological processes for recovery of metals and hence is considered as eco-friendly and cost-effective procedure to remove contaminants from wastewater. The utilization of Azolla has remained limited in agriculture due to its sensitivity to high temperatures, light intensity, composition of growth medium and difficult production technology. The use of Azolla is beneficial due to its reliance on natural resources and utility for flooded rice production as well as phytoremediation potential in agro-environment.